(untitled) (Indonesian Journal of Civil Engineering Study, 2024)
The structural planning for the Poncol Apartment Building is planned to create safe and comfortable housing due to the increasing need for housing as a result of the urbanization phenomenon in Semarang City. The planning of this building meets Indonesian National Standards (SNI) so that it can be categorized as a safe residence. Calculations using SNI 1726:2019 (Earthquake Resistance Research Procedures for Building and Non-Building Structures), SNI 2847:2019 (Structural Load Requirements for Buildings), SNI 1727:2020 (Minimum Design Loads and Related Criteria for Buildings and Other Structures), and with the help of the ETABS program. The calculation results include plates 1 to 5 using a thickness of 120 mm with D10-125 mm reinforcement, beams with dimensions of 40 x 60 cm and 35 x 50 cm, and columns with dimensions of 70 x 70 cm, 50 x 50 cm, and 35 x 35 cm. The deviation values ​​between floors are in below the permit value so that the structure is safe.